Variations of permafrost under freezing and thawing conditions in the coastal catchment Fuglebekken (Hornsund, Spitsbergen, Svalbard). (6th April 2022) - Majdański, Mariusz; Dobiński, Wojciech; Marciniak, Artur; Owoc, Bartosz; Glazer, Michał; Osuch, Marzena; Wawrzyniak, Tomasz
Abstract: Two seismic field surveys were organized in the Fuglebekken coastal catchment of Hornsund, Spitsbergen, Svalbard, to map frozen and unfrozen ground and assess the spatial and temporal state of the permafrost. Surveys were conducted during maximum thawing in September and maximum freezing in April of the following year. The obtained seismic wavefields were interpreted using three methods: the dispersion of surface waves, seismic refraction, and travel time tomography. The seismic experiments were supported by nearby boreholes with continuous thermal monitoring. In the frozen survey, a gradual increase in ice content of water‐filled sediments was found, farther from the coast. In September the shallow sensors in the boreholes validated positive ground temperatures down to 3.0 m depth, with below‐zero temperatures at greater depths. However, seismic tomography indicated that the ground was unfrozen down to 30 m. The ground probably remained unfrozen due to intrusion of high‐salinity seawater, even though it had been below 0°C. In April, in the area 300 m and farther from the coast, the ground below 3 m depth was frozen, except for a 19‐m‐deep open talik identified in a borehole at the slope of Fugle Mountain. We attribute the complex spatial extent, form, and condition of permafrost in the Fuglebekken coastal catchment to multiple factors, including variable solar energy, snow and ground cover, thermal and humidity properties of the soil, subsurface water flow, and seawater intrusion. The presented combination of seismic methods provides a new robust and precise approach to assess the spatial variability of permafrost in a coastal environment. The proposed interpretation shows deep percolation of subsurface flow into permafrost and its seasonal unfreezing at a depth of 30 m in both the zone of saltwater intrusion and the slope area.